Habitual caffeine consumption does not interfere with the acute caffeine supplementation effects on strength endurance and jumping performance in trained individuals - de Salles Painelli, V.; Teixeira, E. L.; Tardone, M.; Moreno, M.; Morandini, J.; Larrain, V. H.; Pires, F. O. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
The long-standing caffeine habituation paradigm was never investigated in strength endurance and jumping exercise performance through a straightforward methodology. The authors examined if habitual caffeine consumption would influence the caffeine ergogenic effects on strength endurance and jumping performance as well as perceptual responses. Thirty-six strength-trained individuals were mathematically allocated into tertiles according to their habitual caffeine consumption: low (20 ± 11 mg/day), moderate (88 ± 33 mg/day), and high consumers (281 ± 167 mg/day). Then, in a double-blind, crossover, counterbalanced fashion, they performed a countermovement vertical jump test and a strength endurance test either after caffeine (6 mg/kg) and placebo supplementation or after no supplementation (control). Perceptual responses such as ratings of perceived exertion and pain were measured at the termination of the exercises. Acute caffeine supplementation improved countermovement vertical jump performance (p = .001) and total repetitions (p = .004), regardless of caffeine habituation. Accordingly, analysis of absolute change from the control session showed that caffeine promoted a significantly greater improvement in both countermovement vertical jump performance (p = .004) and total repetitions (p = .0001) compared with placebo. Caffeine did not affect the rating of perceived exertion and pain in any exercise tests, irrespective of tertiles (for all comparisons, p > .05 for both measures). Caffeine side effects were similar in low, moderate, and high caffeine consumers. These results show that habitual caffeine consumption does not influence the potential of caffeine as an ergogenic aid in strength endurance and jumping exercise performance, thus challenging recommendations to withdraw from the habitual caffeine consumption before supplementing with caffeine.